Ethnomedicinal review of Usnakantaka (Echinops echinatus Roxb.) - Maurya, Santosh Kumar; Kushwaha, Ashwini Kumar; Seth, Ankit (Pharmacognosy Reviews)
Echinops echinatus Roxb. (E. echinatus), commonly known as “Usnakantaka,” is a xerophytic herbaceous plant traditionally used as a stimulant to treat use the term Sexual debility in Indian traditional systems of medicine. The roots, leaves, fruit, and bark are extensively used in folk medicine as well as in Ayurveda. Also, the plant shows a wide range of pharmacological activities such as antifungal, analgesic, diuretic, reproductive, hepatoprotective, antioxidant, anti‑inflammatory, wound‑healing, antipyretic, and antibacterial properties. Among the several active constituents, apigenin, apigenin‑7‑O‑glucoside, echinaticin, 5,7-dihydroxy-8,4’-dimethoxy-flavanone-5-O-α-L-rhamnopyranosyl-7-O - β-D-arabinopyranosyl-(1→4)-O-β-D-glucopyranoside are the most important in terms of reported pharmacological activities. The current review focuses on the updated information from various scientific studies and reports available in the context of the phytoconstituents and pharmacology of this plant. This review also provides adequate information about the use of this plant in an Indian system of medicine, Ayurveda.
Keywords: Apigenin; Ayurveda; echinaticin; Echinops echinatus; sexual disability